(untitled) (Indian Journal of Biochemistry and Biophysics (IJBB), 2026)
Cadmium (Cd) is a common pollutant in the industry and the environment, which causes serious health effects, especially deleterious liver injury. Hesperetin (Hp) is a bioflavonoid with various pharmacological properties, including antioxidant, anti-inflammatory, antiallergic, vasoprotective, anticarcinogenic, and hypolipidemic activities. The present study aimed to investigate the potential role of Hp on Cd-induced hepatic injury in male Wistar rats. The liver tissue was subjected to the comet assay, immunohistochemistry, transmission electron microscopy (TEM), and western blotting. Results of the study showed that rats treated with Cd alone displayed significantly altered markers of oxidative stress (comet assay), inflammation, apoptosis, and hepatic tissue histology compared with controls. Oral co-treatment with Cd to Hpexposed rats for 3 weeks significantly ameliorated the changes. It was remarkably synthesized that Hp could bind to critical apoptotic and inflammatory proteins. It was bridged to Bcl-2 by three hydrogen bonds, with binding energies of –7.2 and –8.3 kcal/mol. It also established hydrogens bonds with Bax, IL-6, and TNF-α were –6.3, –6.6, and -6.2 kcal/mol, respectively. It suggested that Hp might be hepatoprotective and modulate oxidative stress, inflammation, and apoptosis in vivo and in silico.